Pelatihan Spa Bagi Karang Taruna Desa Adat Sumerta Kaja Guna Meningkatkan Kualitas Ekonomi - Ni Putu Isha Aprinica; I Gusti Ayu Melistyari Dewi; Ida Ayu Gayatri Kesumayathi (jurnal ABDIMAS Indonesia, 2024)
Sumerta Kaja Traditional Village is one of the traditional villages in Bali which has quite large tourism potential. The beauty of traditional Balinese spa culture is one of the main attractions for tourists visiting this area. However, in this traditional village there is a group of PKK women who have limited knowledge and skills to develop independent economic businesses. Therefore, spa training for the Sumerta Kaja Traditional Village youth organization is important in order to improve their economic quality. This village has significant tourism potential, but the youth organizations in this traditional village are still unable to utilize this potential optimally. They have limited knowledge and skills in the spa sector, making it difficult for them to be involved in developing the tourism sector in their traditional villages. Apart from that, youth organizations are also a group that has an important role in the family and society. Through spa training, they can be economically empowered and have the opportunity to earn additional income. This will give them pride and increase their role and self-confidence in society.